Distribution, abundance and environmental conditions of the clonal aquatic fern Salvinia natans (L.) All. in the Vistula delta (Baltic Sea Region) - Gałka, Agnieszka; Szmeja, Józef (Biodiversity: Research and Conservation, 2013)
We examined the distribution, resources and environmental conditions of the clonal aquatic fern Salvinia natans (L.) All., expansive in the Vistula delta (N Poland). Before 2006, there were 7 stands of this species, while in the years 2006-2010 their number increased to 21. The most abundant populations were found in the rivers: Tuga (133.0±37.6 indiv./0.1 m2), Fiszewka( 79.3±6.0), Szkarpawa (74.7±5.0), Struga Orłowska (61.0±2.0), Nogat (52.3±2.5), Elbląg (40.3±31.8), Wiślano-Zalewowy Canal (61.3±3.2) and in the SW part of Lake Druzno (72.3±2.5). S. natans did not colonise the weakly saline Vistula Lagoon and Elbląg Bay, which belong to the Baltic Sea. The plant under study occurred in shallow (2.2±1.5 m), narrow (17.9±13.6 m), slow-flowing (0.11±0.12 m s-1) and fertile (4.7±4.2 mg TN dm-3, 0.7±0.4 mg TP dm-3) watercourses. The water in them had neutral or alkaline pH (7.2-9.2) and was weakly saline (53.8±21.3 mg Cl dm-3). A dense mat of S. natans significantly affected the environmental conditions in the watercourses: water oxygenation, PAR intensity and concentration of biogenic substances, especially phosphorus, decreased.